Lactate production yield from engineered yeasts is dependent from the host background, the lactate dehydrogenase source and the lactate export - Branduardi, Paola (BioMed Central, 2006)
BACKGROUND: Metabolic pathway manipulation for improving the properties and the productivity of microorganisms is becoming a well established concept. For the production of important metabolites, but also for a better understanding of the fundamentals of cell biology, detailed studies are required. In this work we analysed the lactate production from metabolic engineered Saccharomyces cerevisiae cells expressing a heterologous lactate dehydrogenase (LDH) gene. The LDH gene expression in a budding yeast cell introduces a novel and alternative pathway for the NAD(+ )regeneration, allowing a direct reduction of the intracellular pyruvate to lactate, leading to a simultaneous accumulation of lactate and ethanol. RESULTS: Four different S. cerevisiae strains were transformed with six different wild type and one mutagenised LDH genes, in combination or not with the over-expression of a lactate transporter. The resulting yield values (grams of lactate produced per grams of glucose consumed) varied from as low as 0,0008 to as high as 0.52 g g(-1). In this respect, and to the best of our knowledge, higher redirections of the glycolysis flux have never been obtained before without any disruption and/or limitation of the competing biochemical pathways. CONCLUSION: In the present work it is shown that the redirection of the pathway towards the lactate production can be strongly modulated by the genetic background of the host cell, by the source of the heterologous Ldh enzyme, by improving its biochemical properties as well as by modulating the export of lactate in the culture media.